2015
DOI: 10.4103/0975-7406.155797
|View full text |Cite
|
Sign up to set email alerts
|

Whats special in a child′s larynx?

Abstract: What's special in a child's larynx? Many of us know only a few specialties of the pediatric larynx, but there are much more features, which are unique and often not highlighted. To understand the pediatric larynx, we have reviewed the development, the functions in-utero and new born period and peculiarities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…27 This mixture was hydrolyzed to obtain lupeol (yield 50%) that was characterized by NMR and IR spectroscopy besides comparison with authentic sample. 28,29 Lupeol was used as the starting material for all chemical reactions presented in this paper. A total of 6 new lupeol derivatives, whose structures are depicted in Scheme 1, were synthesized.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…27 This mixture was hydrolyzed to obtain lupeol (yield 50%) that was characterized by NMR and IR spectroscopy besides comparison with authentic sample. 28,29 Lupeol was used as the starting material for all chemical reactions presented in this paper. A total of 6 new lupeol derivatives, whose structures are depicted in Scheme 1, were synthesized.…”
Section: Resultsmentioning
confidence: 99%
“…22 Its IR spectrum showed characteristic bands in These signals confirm the insertion of a propargyl group in the lupeol structure. 22 The spectrum of 13 displayed common signals with lupeol, 28,29 The CuAAC, often referred to as "click reaction", occurred between the terminal alkyne of the lupeol propargyl ether (13) and known organic azides [17][18][19]21 that were previously synthesized. 22 CuAAc is known for its high efficiency without need for special reaction conditions, such as high temperature and/or high pressure, and is regioselective giving only the 1,4-disubstituted isomer.…”
Section: Resultsmentioning
confidence: 99%
“…Our results indicated that these airway events occurred more frequently in the pediatric population, a finding that is echoed in other studies . This may in part be due to the unique anatomic and physiologic challenges encountered in the pediatric airway, where unprepared hands during an unanticipated emergency may me more likely to result in malpractice . Furthermore, tonsillectomy/adenoidectomy was the most common procedure involved in this report, a surgery performed primarily on children.…”
Section: Discussionmentioning
confidence: 99%
“…6,9 This may in part be due to the unique anatomic and physiologic challenges encountered in the pediatric airway, where unprepared hands during an unanticipated emergency may me more likely to result in malpractice. 10 Furthermore, tonsillectomy/adenoidectomy was the most common procedure involved in this report, a surgery performed primarily on children. It has been found to be one of the most commonly litigated surgeries as over 700 000 are performed every year, and it involves inherent complications that, although rare, can result in devastating morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Repeated column chromatography of the bioactive fractions resulted in the isolation of 10 compounds, out of which compounds 1e5 were new compounds and structures were established using IR, MS, 1D and 2D NMR (HSQC, HMBC, COSY, and NOESY) spectroscopic techniques. The other five known compounds were identified as Piscidinone A (6), 11 Piscidinol C (7), 9d Piscidinol D (8), 6a Piscidinol E (9), 9e and Lupeol (10) 12 1.13, 1.16, 1.17, 1.28, 1.47, and 1.65 (3H each, s), which correlated with the carbons at d C 21. 4, 27.5, 18.8, 20.3, 26.8, 19.5, and 24.7 13 implied that their structures were closely related, with the marked difference being a presence of a carbonyl group at C-7 (B-ring) instead of an acetoxyl group.…”
Section: Isolation and Structure Elucidation Of New Compoundsmentioning
confidence: 97%